Penerapan Model Pembelajaran Cooperative Learning Tipe STAD Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V SD Negeri 2 Seraya Barat - Ni Kadek Suartini (Jayapangus Press, 2019)
This classroom action research aims to: Improve student learning outcomes after the implementation of the STAD type cooperative learning model in students of class V SD Negeri 2 Seraya Barat academic year 2016/2017. Especially in the material properties of light. This research was conducted by class action research method with cooperative learning model or cooperative learning type STAD (Student Teams Achievement Divisions) conducted in students of class V SD Negeri 2 Seraya Barat with the number of students 17 students in science subjects. This research was conducted in two cycles. The research instrument uses a test method to analyze student learning outcomes for the given learning model. Based on the results of preliminary observations compared to the tests carried out in Cycle I and Cycle II obtained the average student learning outcomes that have increased. It can be explained that student learning outcomes from the initial pre-cycle / test is still low because it is still below the KKM with a 57 grade average. After the cooperative learning model or cooperative learning type STAD (Student Teams Achievement Divisions) is applied, in the first cycle the class average experiences the increase becomes 64, and the second cycle reaches 84. The classical completeness automatically increases. Then it can be concluded that the implementation of the cooperative learning model or cooperative learning type STAD (Student Teams Achievement Division) was successfully applied to science learning in students of class V SD Negeri 2 Seraya Barat.